MRI‐based measurements of whole‐brain global cerebral blood flow: Comparison and validation at 1.5T and 3T - Chen, Chun‐Ming; Huang, Yen‐Chih; Shih, Cheng‐Ting; Chen, Yung‐Fang; Peng, Shin‐Lei (Journal of magnetic resonance imaging, 2018)
Background Whole‐brain global cerebral blood flow (CBF) determined by MRI techniques, calculated using total CBF (TCBF) from phase‐contrast MRI (PC‐MRI), and brain parenchyma volume (BPV) from T1‐weighted image, have become increasingly popular in many applications. Purpose/Hypothesis To determine if MRI‐based measurements of whole‐brain global CBF data obtained across different field strengths could be merged, TCBF and BPV data acquired at 1.5T and 3T were compared. Study Type Prospective study. Population Seventeen healthy subjects (eight females, aged 21–29 years old). Field Strength/Sequence Fast spoiled gradient echo (FSPGR) and PC‐MRI at both 1.5T and 3T. Assessment TCBF and BPV data acquired at 1.5T and 3T were compared. Statistical Tests The relationships of TCBF and whole‐brain global CBF between two field strengths were examined by using the Pearson correlation coefficient analysis and intraclass correlation coefficient (ICC). Results Regression analysis revealed a strong correlation between TCBF at two field strengths (R2 = 0.78, P < 0.001), and the ICC was 0.85, suggesting measurements of TCBF at 1.5T were comparable and correlated with those at 3T. There was a significant difference in BPV between field strengths, where the white matter estimate was significantly larger at 1.5T when compared with that at 3T (P < 0.001). When TCBF was further normalized to the brain parenchyma mass to obtain whole‐brain global CBF, it only showed a moderate correlation between measurements at the two field strengths (R2 = 0.46, P = 0.003) and lower ICC of 0.66, reflecting the slightly higher interstrength variability in the whole‐brain global CBF measurements. Data Conclusion TCBF measurements could be performed equally well with comparable results at both field strengths, but specific attention should be given when TCBF is further normalized to BPV to obtain whole‐brain global CBF. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:1273–1280.